Exploring the Role of Artificial Intelligence in Fostering Ethical Business Practices: Insights from Digital Marketing Advancements in Indonesia - Aretha Widi Ailani (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This study investigates the utilization of Artificial Intelligence (AI) to promote ethical business practices within the evolving landscape of digital marketing in Indonesia. The research aims to elucidate the current state of AI integration, its impact on ethical considerations, and the challenges and opportunities it presents. The study adopts a qualitative approach, employing semi-structured interviews and focus group discussions with key stakeholders involved in digital marketing and AI development. Sampling techniques include purposive sampling to ensure representation across industries and snowball sampling to access knowledgeable participants. Data analysis follows thematic analysis principles, identifying recurring patterns, themes, and divergences related to ethical concerns and AI implementation. Preliminary findings indicate a nuanced relationship between AI adoption and ethical dilemmas, with emerging strategies to balance innovation with ethical principles. This study contributes to understanding the ethical implications of AI in digital marketing and offers insights for businesses, policymakers, and scholars aiming to navigate this complex terrain responsibly.